Exploring English Language Students’ Difficulties in Listening Comprehension - Rameshwar Jyoti (Newinera Publisher, 2020)
Listening skill is one of the four major skills of language that most language learners desire to get mastery in order to communicate effectively in different contexts. It is one of the most challenging skills for many students. The main aim of this study, therefore, was to explore English language students’ listening comprehension difficulties. I employed a survey research design as a research method. Randomly selected sixty male and sixty female students studying English at three community schools of Rupandehi district, Nepal took part in this study as research respondents. They all were from secondary level. A closed ended questionnaire with 24 items on students' listening problem was administered to elicit the data from the respondents. The results of questionnaire indicated that content of the listening text (e.g., unfamiliar words, idiom, feeling fatigue while listening to the long text) was the major source of listening difficulties for the students. The second source of difficulty was related to the listener that included lack of concentration with long listening text and existence of noise in the place. The third difficulty included linguistic features such as complex grammatical structures, pronunciation and problems in distinguishing the word boundaries. And the last source of listening problem was concerned with speaker’s speed of speech and different accents. The findings also raise awareness of both teachers and students regarding the listening comprehension problems.